Strategi Pengelolaan dan Pemanfaatan Tanah Wakaf Desa Sumpang Mango Kabupaten Sidenreng Rappang - Trisno Wardy Putra; Nur Hikmah (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2021)
Background. The management of waqf in Sumpang Mango village is the same as the management of waqf in general Indonesia. The waqf in this village is accommodated by the KUA of Pitu Riawa and the village government of Sumpang Mango. Aim. This study aims to examine and determine the strategic description of the management and utilization of waqf land in the village of Sumpang Mango. Methods. The method used in this research is field research with a qualitative approach. Results. The results obtained from this research are that the management of waqf in Sumpang Mango village is already semi-professional and administrative issues are quite good. What needs to be emphasized is the socialization of waqf from the KUA Pitu Riawa or other parties.